2018
DOI: 10.1111/sed.12452
|View full text |Cite
|
Sign up to set email alerts
|

Down‐slope facies variability within deep‐water channel systems: Insights from the Upper Cretaceous Cerro Toro Formation, southern Patagonia

Abstract: In southern Patagonia, outcrops of the Upper Cretaceous Cerro Toro Formation preserve a >150 km long deep‐water axial channel belt in the Magallanes–Austral Basin, providing a unique opportunity to investigate longitudinal variations in the depositional characteristics of a deep‐water channel system. This study documents sedimentological, stratigraphical and geochronological data from the Cerro Toro Formation in the Argentine sector of the basin. New results are integrated with previous work from the Chilean b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 85 publications
1
17
0
1
Order By: Relevance
“…Conglomeratic channel‐levée deposits up to 6 to 8 km wide and 600 to 1000 m thick are found in foreland basin deposits such as the Cerro Toro Formation in the Magallanes Basin, Chile (Crane & Lowe, ; Hubbard et al ., ; Bernhardt et al ., ) and the Puchkirchen Formation in the Molasse Basin, Upper Austria (Hubbard et al ., ; Sharman et al ., ). Unlike the Geoffrey Formation submarine conduits, these foreland‐related channel‐systems are generally oriented parallel to basin axes (De Ruig & Hubbard, ; Jobe et al ., ; Malkowski et al ., ). Development of the Cerro Toro axial system is generally linked to a major phase of thrusting in the Andean fold–thrust belt (Romans et al ., ).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Conglomeratic channel‐levée deposits up to 6 to 8 km wide and 600 to 1000 m thick are found in foreland basin deposits such as the Cerro Toro Formation in the Magallanes Basin, Chile (Crane & Lowe, ; Hubbard et al ., ; Bernhardt et al ., ) and the Puchkirchen Formation in the Molasse Basin, Upper Austria (Hubbard et al ., ; Sharman et al ., ). Unlike the Geoffrey Formation submarine conduits, these foreland‐related channel‐systems are generally oriented parallel to basin axes (De Ruig & Hubbard, ; Jobe et al ., ; Malkowski et al ., ). Development of the Cerro Toro axial system is generally linked to a major phase of thrusting in the Andean fold–thrust belt (Romans et al ., ).…”
Section: Discussionmentioning
confidence: 97%
“…The integration of high‐resolution geochronological data with regional stratigraphy has recently been applied to provide novel insight into deep‐water sediment routing in ancient systems (e.g. Sharman et al ., ; Malkowski et al ., ). Several studies have demonstrated the importance of large ( n ≥ 300) detrital zircon datasets for consistent and reliable identification of detrital zircon populations and their relative proportions within a sample (e.g.…”
Section: Detrital Zircon Geochronology Methodsmentioning
confidence: 97%
“…B; Fonnesu et al., ). A more detailed assessment of the presence or absence of grooves at the base of hybrid event beds is not possible at present, as grooves are often reported for entire outcrop sections, usually as palaeocurrent indicators, rather than specifically linked to hybrid beds (Spychala et al., , 2017b ; Malkowski et al., , ), or tool marks are treated as a single category, and thus grooves are not specified (e.g. Hodgson, ).…”
Section: Tool Marksmentioning
confidence: 99%
“…Numerical dating using detrital-zircon geochronology provides a powerful tool to determine the timing of sedimentation from deep-time strata (e.g., Dickinson and Gehrels, 2009;Spencer et al, 2012;Schwartz et al, 2017;Daniels et al, 2018;Malkowski et al, 2018). We use detritalzircon geochronology data to identify and temporally constrain the stratigraphic evolution of a long-lived (>10 6 yr) Cretaceous submarine slope-channel system that crops out on Hornby and Denman Islands in British Columbia, Canada.…”
Section: ■ Introductionmentioning
confidence: 99%